Influenza increases invasive meningococcal disease risk in temperate countries. (September 2020) - Salomon, A.; Berry, I.; Tuite, A.R.; Drews, S.; Hatchette, T.; Jamieson, F.; Johnson, C.; Kwong, J.; Lina, B.; Lojo, J.; Mosnier, A.; Ng, V.; et al.
Abstract: Objectives: Invasive meningococcal disease (IMD) is a severe bacterial infection that displays wintertime seasonality in temperate countries. Mechanisms driving seasonality are poorly understood and may include environmental conditions and/or respiratory virus infections. We evaluated the contribution of influenza and environmental conditions to IMD risk, using standardized methodology, across multiple geographical regions. Methods: We evaluated 3276 IMD cases occurring between January 1999 and December 2011 in 11 jurisdictions in Australia, Canada, France and the United States. Effects of environmental exposures and normalized weekly influenza activity on IMD risk were evaluated using a case-crossover design. Meta-analytic methods were used to evaluate homogeneity of effects and to identify sources of between-region heterogeneity. Results: After adjustment for environmental factors, elevated influenza activity at a 2-week lag was associated with increased IMD risk (adjusted odds ratio (OR) per standard deviation increase 1.29; 95% confidence interval, 1.04–1.59). This increase was homogeneous across the jurisdictions studied. By contrast, although associations between environmental exposures and IMD were identified in individual jurisdictions, none was generalizable. Conclusions: Using a self-matched design that adjusts for both coseasonality and case characteristics, we found that surges in influenza activity result in an acute increase in population-level IMD risk. This effect is seen across diverse geographic regions in North America, France and Australia. The impact of influenza infection on downstream meningococcal risk should be considered a potential benefit of influenza immunization programmes.